Budaya Organisasi sebagai Faktor Penentu Keberhasilan Manajemen Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
The success of Islamic educational management is determined not only by the effectiveness of managerial functions but also by an institution's ability to establish an organizational culture that integrates Islamic values with contemporary governance practices. Various institutional challenges, including low organizational commitment, ineffective coordination, resistance to change, and suboptimal policy implementation, indicate that organizational culture exerts a substantial influence on the quality of Islamic educational management. This study aims to examine the role of organizational culture as a determining factor in the success of Islamic educational management through a comprehensive conceptual analysis. The research employed a qualitative method using a library research approach. The data were collected from academic books, nationally accredited journals, internationally reputable journals, conference proceedings, and other scholarly documents relevant to organizational culture and Islamic educational management. Data were analyzed using qualitative content analysis through the stages of data reduction, thematic categorization, conceptual synthesis, critical interpretation, and conclusion drawing. The findings reveal that organizational culture functions as an institutional mechanism that internalizes organizational values into all managerial processes, thereby fostering alignment between institutional objectives and the behavior of organizational members. Furthermore, organizational culture develops adaptive capacity that promotes innovation, organizational learning, and institutional resilience in responding to the dynamic educational environment. In addition, it serves as a strategic asset that strengthens leadership effectiveness, human resource professionalism, quality assurance systems, and the sustainability of Islamic educational institutions. The study concludes that organizational culture constitutes the fundamental foundation for developing Islamic educational governance that is effective, adaptive, integrity-driven, and oriented toward continuous quality improvement. Therefore, strengthening organizational culture should be positioned as a strategic priority in advancing Islamic educational management to establish educational institutions that are competitive, credible, and sustainable in the face of ongoing global transformation.